2013
DOI: 10.1155/2013/401565
|View full text |Cite
|
Sign up to set email alerts
|

Bats, Fever and Adenopathy – What Is the Link?

Abstract: A case of travel-related, subacute, progressive disseminated histoplasmosis in a nonimmunocompromised individual is described. The present case highlights the environmental exposure to Histoplasma capsulatum in Costa Rica, the diagnostic approach and treatment options, as well as new alternatives for salvage therapy for histoplasmosis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…1,6,7 Since the first isolation by Emmons, [8][9][10] numerous studies have confirmed the presence of H. capsulatum in soils rich in nitrogen and phosphorus, such as soils containing bird and bat excrement. [10][11][12][13][14] In 1968, Lockwood and Garrison 15 demonstrated the ability of H. capsulatum to grow with different concentrations of nitrogen (N), which was shown to promote fungal growth. The same year, Brandsberg 16 described fungi isolated together from soils harboring H. capsulatum, but the author noted that a more complete physicochemical and microbiological characterization of the soils where H. capsulatum was isolated was needed to identify areas with a greater risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,7 Since the first isolation by Emmons, [8][9][10] numerous studies have confirmed the presence of H. capsulatum in soils rich in nitrogen and phosphorus, such as soils containing bird and bat excrement. [10][11][12][13][14] In 1968, Lockwood and Garrison 15 demonstrated the ability of H. capsulatum to grow with different concentrations of nitrogen (N), which was shown to promote fungal growth. The same year, Brandsberg 16 described fungi isolated together from soils harboring H. capsulatum, but the author noted that a more complete physicochemical and microbiological characterization of the soils where H. capsulatum was isolated was needed to identify areas with a greater risk of infection.…”
Section: Introductionmentioning
confidence: 99%